Hermite‐Hadamard type inequalities for generalized Riemann‐Liouville fractional integrals of h‐convex functions - Dragomir, Silvestru Sever (Mathematical methods in the applied sciences, 2021)
In this paper, we establish some Hermite‐Hadamard type inequalities for the Generalized Riemann‐Liouville fractional integrals Ia+,gαf and Ib−,gαf, where g is a strictly increasing function on a,b, having a continuous derivative on a,b and under the assumption that the composite function f∘g−1 is h ‐convex on ga,gb. Some applications for Hadamard fractional integrals and s‐Godunova‐Levin type convex functions are also provided.